2015
DOI: 10.1039/c5ce01004g
|View full text |Cite
|
Sign up to set email alerts
|

The effects of molecular flexibility and substituents on conformational polymorphism in a series of 2,5-diamino-3,6-dicyanopyrazine dyes with highly flexible groups

Abstract: The flexibility of the dibenzylamino groups and the terminal substituents played an important role in the conformational polymorphism of diaminodicyanopyrazine dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…There is also a large difference in the spatial location of Ph1 with respect to the hydroquinone ring. The molecular structures of the two polymorphs suggested that the flexibility of the dibenzylamino groups contributes to the conformational variety of (1), similar to previous reports (Akune et al, 2015(Akune et al, , 2017. The dibenzylamino groups also affected the molecular packing structures of both polymorphs.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…There is also a large difference in the spatial location of Ph1 with respect to the hydroquinone ring. The molecular structures of the two polymorphs suggested that the flexibility of the dibenzylamino groups contributes to the conformational variety of (1), similar to previous reports (Akune et al, 2015(Akune et al, , 2017. The dibenzylamino groups also affected the molecular packing structures of both polymorphs.…”
Section: Resultssupporting
confidence: 84%
“…In this article, we report a new example of conformational poly- ISSN 2053ISSN -2296 # 2018 International Union of Crystallography morphism of an aromatic compound having dibenzylamino groups, namely 2,5-dichloro-3,6-bis(dibenzylamino)-p-hydroquinone, (1) (see Scheme 1). We have confirmed that the dibenzylamino group plays an important role as a flexible substituent in the occurrence of polymorphism when it is attached to an aromatic moiety (Akune et al, 2015).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…In addition, derivatives with Cl/Br-substituted benzyl groups also exhibit polymorphism (existing as red, orange, and yellow forms) [31], with their crystal structures suggesting that the colour change is caused by molecular deformation. Moreover, the halogen substituents of benzyl groups significantly influence the above phenomenon by affecting intermolecular interactions in the crystal structure [32,33]. These results imply that halogen substituents that do not influence the fluorophore electronic states can contribute to the tuning of solid-state colour and fluorescence properties of pyrazine dyes.…”
Section: Introductionmentioning
confidence: 92%
“…1) bearing benzyl groups mono-substituted with halogen (F, Cl, Br, or I) or methyl moieties and evaluated the effect of halogen substituents on the solid-state fluorescence properties of these dyes. In addition to 1, 2b, 2c, 2e, and 3a-3e, which have been synthesised and identified previously [31][32][33], we newly prepared para-substituted F-(2a) and I-derivatives (2d) to systematically characterise the effect of terminal substituents on their solid-state fluorescence properties.…”
Section: Introductionmentioning
confidence: 99%